The biomimetic design and 3D printing of customized mechanical properties porous Ti6Al4V scaffold for load-bearing bone reconstruction. (15th August 2018) - Zhang, Boqing; Pei, Xuan; Zhou, Changchun; Fan, Yujiang; Jiang, Qing; Ronca, Alfredo; D'Amora, Ugo; Chen, Yu; Li, Huiyong; Sun, Yong; Zhang, Xingdong
Abstract: The Ti6Al4V alloy is one of the most commonly used in orthopedic surgery. Mechanical property of implant contributes important biological functions for load-bearing bone tissue reconstruction. There is a significant need for design and fabrication of porous scaffold with customized mechanical properties for bone tissue engineering. In this paper, bionic design and fabrication of porous implants were studied by using finite element analysis (FEA) and 3D printing techniques. Novel porous architectures were built up with diamond lattice pore structure arraying units. With finite element analysis, the structure weak points under pressure were simulated so that the mechanical properties of the implants were optimized. Porous implants with different porosities and mechanical properties were precisely fabricated by selected laser melting (SLM), one of powder bed fusion additive manufacturing techniques. The biocompatibility and repair effect were studied by in vivo experiments. Animal results indicated that the damaged load-bearing bones were well reconstructed. New generated bones embedded and fitted into the designed porous implants. The optimized design and precisely manufactured implants are conducive to bone tissue repair and reconstruction. Graphical abstract: Unlabelled Image Highlights: Scaffolds showed biomimetic structure design and customized mechanical properties. Scaffolds with 66.1%–79.5% porosity were biomimetic designed by using diamond lattice pore units array formation. Scaffolds within a wide range of compressive strength from 36 to 140 MPa were successfully fabricated. Animal results indicated that the damaged load-bearing bones were well reconstructed.